2020
DOI: 10.3390/diagnostics10100808
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Innate Lymphoid Cells in the Regulation of Immune Homeostasis in Sepsis-Mediated Lung Inflammation

Abstract: Septic shock/severe sepsis is a deregulated host immune system response to infection that leads to life-threatening organ dysfunction. Lung inflammation as a form of acute lung injury (ALI) is often induced in septic shock. Whereas macrophages and neutrophils have been implicated as the principal immune cells regulating lung inflammation, group two innate lymphoid cells (ILC2s) have recently been identified as a new player regulating immune homeostasis. ILC2 is one of the three major ILC subsets (ILC1s, ILC2s,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
(105 reference statements)
0
6
1
Order By: Relevance
“…The roles of ILC2s in the lung inflammation induced by sepsis have been reported. ILC2, the most abundant ILC subset in the lungs, secretes type 2 cytokines such as IL-5 and IL-13, thereby playing the important roles in the regulation of type 2 immune responses, which is required for resolving inflammation and remodeling tissues ( 110 ). Insufficient resolution of inflammation and aberrant regulation of tissue repair and remodeling causes acute lung injury (ALI), and lung fibrosis, leading to the irreversible destruction of pulmonary functions.…”
Section: Pd-1/pd-l As a Novel Therapeutic Target To Reverse Immune Pamentioning
confidence: 99%
“…The roles of ILC2s in the lung inflammation induced by sepsis have been reported. ILC2, the most abundant ILC subset in the lungs, secretes type 2 cytokines such as IL-5 and IL-13, thereby playing the important roles in the regulation of type 2 immune responses, which is required for resolving inflammation and remodeling tissues ( 110 ). Insufficient resolution of inflammation and aberrant regulation of tissue repair and remodeling causes acute lung injury (ALI), and lung fibrosis, leading to the irreversible destruction of pulmonary functions.…”
Section: Pd-1/pd-l As a Novel Therapeutic Target To Reverse Immune Pamentioning
confidence: 99%
“…Recently a small subset of other immune cells was identified in the lung, namely, innate lymphoid cells (ILCs), which are distinct from T and B lymphocytes. ILC1s, ILC2s, and ILC3s act as the innate counterparts of the traditional Th (CD4 + T helper) 1, Th2, and Th17 T cell effector subsets, respectively [ 1 ]. Furthermore, ILCs and traditional T cells also share a common ontogeny [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ILC2 plays an important role in regulating adaptive immunity, macrophage polarization, etc ( 27 , 28 ). The results of the Go enrichment analysis ( Figure 4F ) showed that DEGs of ILC2 were mainly focused on regulating innate immune cells, including regulating the myeloid cell differentiation, and positive regulation of cytokine ( 18 ).…”
Section: Resultsmentioning
confidence: 99%